2018
DOI: 10.15252/embj.2018100072
|View full text |Cite
|
Sign up to set email alerts
|

Tissue tension and not interphase cell shape determines cell division orientation in the Drosophila follicular epithelium

Abstract: We investigated the cell behaviors that drive morphogenesis of the Drosophila follicular epithelium during expansion and elongation of early‐stage egg chambers. We found that cell division is not required for elongation of the early follicular epithelium, but drives the tissue toward optimal geometric packing. We examined the orientation of cell divisions with respect to the planar tissue axis and found a bias toward the primary direction of tissue expansion. However, interphase cell shapes demonstrate the opp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 76 publications
(150 reference statements)
7
57
0
Order By: Relevance
“…In egg chambers, Finegan et al (2019) found that during the phase of biased division orientation, apical myosin coalesces in multicellular nodes, consistent with the idea that tissuelevel force is generated by myosin contractility. They first asked whether known differences in follicle cell shape and behavior at the poles versus at the equator (Alegot et al, 2018) reflect differences in tissue tension across these two areas.…”
supporting
confidence: 77%
See 4 more Smart Citations
“…In egg chambers, Finegan et al (2019) found that during the phase of biased division orientation, apical myosin coalesces in multicellular nodes, consistent with the idea that tissuelevel force is generated by myosin contractility. They first asked whether known differences in follicle cell shape and behavior at the poles versus at the equator (Alegot et al, 2018) reflect differences in tissue tension across these two areas.…”
supporting
confidence: 77%
“…In other tissues, tissue-level apical cortical tension is mediated by the actomyosin cytoskeletonanchored cell-cell by cell junctions; e.g., in germband-extending Drosophila embryos, planar-polarized multicellular myosin cables and oppositely planar-polarized junctional proteins drive cell rearrangements. In egg chambers, Finegan et al (2019) found that during the phase of biased division orientation, apical myosin coalesces in multicellular nodes, consistent with the idea that tissuelevel force is generated by myosin contractility. However, adherens junction proteins and the junction-cytoskeleton linker Canoe did not exhibit obvious planar polarity.…”
supporting
confidence: 77%
See 3 more Smart Citations